Effect of super dosing of phytase on growth performance, ileal digestibility and bone characteristics in broilers fed corn–soya‐based diets. Issue 1 (28th April 2015) - Manobhavan, M.; Elangovan, A. V.; Sridhar, M.; Shet, D.; Ajith, S.; Pal, D. T.; Gowda, N. K. S.
Summary: A feeding trial was designed to assess the effect of super dosing of phytase in corn–soya‐based diets of broiler chicken. One hundred and sixty‐eight day‐old broilers were selected and randomly allocated to four dietary treatment groups, with 6 replicates having 7 chicks per treatment group. Two‐phased diets were used. The starter and finisher diet was fed from 0 to 3 weeks and 4 to 5 weeks of age respectively. The dietary treatments were consisted of normal phosphorus (NP) group without any phytase enzyme (4.5 g/kg available/non‐phytin phosphorus (P) during starter and 4.0 g/kg during finisher phase), three low‐phosphorus (LP) groups (3.2 g/kg available/non‐phytin P during starter and 2.8 g/kg during finisher phase) supplemented with phytase at 500, 2500, 5000 FTU/kg diet, respectively, to full fill their phosphorus requirements. The results showed that super doses of phytase (at 2500 FTU and 5000 FTU/kg) on low‐phosphorus diet improved feed intake, body weight gain, ileal digestibility (serine, aspartic acid, calcium, phosphorus), blood P levels and bone minerals such as calcium (Ca), P, magnesium (Mg) and zinc (Zn) content. It could be concluded that super doses of phytase in low‐phosphorus diet were beneficial than the normal standard dose (at 500 FTU/kg) of phytase in diet of broiler chicken.